Pengaruh Penerapan Sistem Absensi Pendeteksi Wajah Dan Pengawasan Atasan Terhadap Disiplin Kerja Pegawai Di Birokesejahteraan Masyarakat Kantor Gubernur Sumatera Utara - Deswina Fitri Indriani; Ahmad Prayudi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the influence of the implementation of a face detection attendance system and superior supervision on employee work discipline at the People's Welfare Bureau of the North Sumatra Governor's Office. Work discipline is a key factor in organizational success, yet preliminary data indicated challenges regarding consistency in attendance and employee compliance. This research adopts a quantitative approach with a causal associative design. The research population consisted of 55 employees, and the entire population was utilized as a sample through a saturated sampling technique. Data were collected via questionnaires and analyzed using multiple linear regression with the assistance of SPSS software. The results of the study show that, partially, the face detection attendance system has a positive and significant effect on work discipline, with a t-statistic of 7.875 and a significance value of 0.000. Similarly, superior supervision has a positive and significant effect, with a t-statistic of 3.017 and a significance value of 0.004. Simultaneously, both variables contribute 64.5% to the variance of work discipline. In conclusion, the integration of modern attendance technology and effective human supervision is essential for establishing optimal civil servant discipline to improve the quality of public services